2020
DOI: 10.1186/s40659-020-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of endothelial function by Gunnera tinctoria extract with antioxidant properties

Abstract: Background Gunnera tinctoria has been collected by Mapuche-Pewenche people for food and medicinal purposes. The high polyphenol content of methanolic extract from G. tinctoria leaves with chemical constituents such as ellagic acid and quercetin derivatives suggests its application to prevent endothelial dysfunction and oxidative stress. The aim of this study was to provide evidence of the protective effect of this extract on endothelial function by reducing oxidative stress induced by high d-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Gallic acid, ellagic acid, catechin, epicatechin, and quercetin have been described as major phenolics of G. tinctoria [ 8 , 20 ], and all of them are widely known for their antioxidant properties. Based on the hypothesis that the phenolic-enriched fraction of G. tinctoria would exert antitumoral activities in breast and pancreatic cancer cell lines, their effects on cell viability, culture growth, and proliferation were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallic acid, ellagic acid, catechin, epicatechin, and quercetin have been described as major phenolics of G. tinctoria [ 8 , 20 ], and all of them are widely known for their antioxidant properties. Based on the hypothesis that the phenolic-enriched fraction of G. tinctoria would exert antitumoral activities in breast and pancreatic cancer cell lines, their effects on cell viability, culture growth, and proliferation were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Dysentery, diarrhea, circulatory and urinary disorders, high respiratory tract diseases, and gynecological, and obstetric problems, are some examples where G. tinctoria is used in folk medicine [ 7 ]. Moreover, antioxidant, dermal anti-inflammatory, and antifungal activities, as well as improvement of the endothelial function are recent therapeutic activities that have been also reported for G. tinctoria [ 8 ]. Based on this, this plant emerges as a particularly interesting natural source of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, Asian countries use turmeric as a spice, safe and beneficial for the body [ 70 , 73 ]. About 90% of the biologically active substances in turmeric is curcumin.…”
Section: Basic Phytonutraceuticalsmentioning
confidence: 99%
“…Rosehip powder is widely used in traditional medicine [ 71 , 73 ]. A meta-analysis of randomized controlled trials (RCT) has shown that rosehip powder reduces pain and reduces the use of analgesics in OA patients [ 51 ].…”
Section: Basic Phytonutraceuticalsmentioning
confidence: 99%
See 1 more Smart Citation